Positive electrode plate, electrode plate assembly, battery monomer, battery and electric device

By layering and controlling material parameters in the positive electrode sheet, the problems of uneven current and low rate performance are solved, and the high rate performance and capacity retention are improved, and both safety performance is achieved.

CN119230770AActive Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310798151.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

When using multiple materials in combination, the existing positive electrode sheets have problems such as uneven current and low rate performance, resulting in a decrease in capacity retention rate in the early cycle.

Method used

By layering the first and second positive electrode active materials in the positive electrode sheet, the powder resistivity and weight ratio are controlled, the conductivity difference is reduced, and a material layer with weak ion transport performance is provided on the surface of the material layer to reduce the The current is uneven, which increases the ion transmission rate.

Benefits of technology

It effectively reduces the electron conduction polarization between the positive electrode sheets, improves the rate performance and capacity retention rate, and has high energy density and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230770A_ABST
    Figure CN119230770A_ABST
Patent Text Reader

Abstract

The invention discloses a positive plate, a pole piece assembly, a battery monomer, a battery and an electric device, and belongs to the technical field of batteries. The positive plate comprises positive electrode active material layers, the positive electrode active material layers comprise a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer comprises a first positive electrode active material, and the second positive electrode active material layer comprises a second positive electrode active material; the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight ratio w1 of the first positive electrode active material and the weight ratio w2 of the second positive electrode active material meet the following relation: # imgabs0 # can reduce the conductivity difference between the first positive electrode active material layer and the second positive electrode active material layer; therefore, the electron conduction polarization between the two layers is reduced, and the rate capability of the whole positive plate is favorably exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, an electrode sheet assembly, a battery cell, a battery and an electrical device. Background Art

[0002] In a positive electrode sheet using multiple positive electrode active materials, in order to reduce the possibility of current unevenness between the positive electrode active materials, the positive electrode active materials are usually arranged in layers. However, the positive electrode sheet after the layered arrangement still has the problem of low rate performance. Summary of the invention

[0003] In view of the above problems, the present application provides a positive electrode sheet, a electrode sheet assembly, a battery cell, a battery and an electrical device, which can reduce the conductivity difference between each positive electrode active material layer and improve the problem of low rate performance.

[0004] In a first aspect, the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the ion transport capacity of the second positive electrode active material is less than the ion transport capacity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in units of Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in units of Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

[0005] In the technical solution of the embodiment of the present application, the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material are controlled to meet To reduce the difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer, thereby reducing the electronic conduction polarization between the two layers, which is beneficial to the rate performance of the entire positive electrode sheet. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle.

[0006] In some embodiments, the powder resistivity r1 of the first positive electrode active material in Ω·cm, the powder resistivity r2 of the second positive electrode active material in Ω·cm, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

[0007] In the above implementation process, the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material are controlled to meet The difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer can be further reduced, which is more conducive to the performance of the rate performance of the entire positive electrode sheet.

[0008] In some embodiments, the powder resistivity of the first positive electrode active material is 500 to 80,000 Ω·cm at 8 MPa; and / or

[0009] The powder resistivity of the second positive electrode active material is 5 to 120 Ω·cm at 8 MPa; and / or

[0010] The weight proportion of the first positive electrode active material in the positive electrode sheet is 0.50-0.95; and / or

[0011] The weight ratio of the second positive electrode active material in the positive electrode sheet is 0.05-0.50.

[0012] In some embodiments, the positive electrode sheet further includes a current collector, the first positive electrode material active layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector.

[0013] In the above implementation process, by placing the second positive electrode active material layer with weaker ion transmission performance on the surface of the first positive electrode active material layer, when used as a battery, the second positive electrode active material layer is closer to the negative electrode sheet, making its ion transmission path shorter, which is conducive to improving its ion transmission rate and thus improving its rate performance. At the same time, when the material of the first positive electrode material active layer is a material that is prone to side reactions, such as a ternary system material, this method can reduce the possibility of side reactions, which is more conducive to the electrochemical performance of the positive electrode sheet.

[0014] In some embodiments, the thickness Hb of the first cathode material active layer is 20 to 70 μm; and / or

[0015] The thickness Ha of the second positive electrode active material layer is 5 to 60 μm.

[0016] In the above implementation process, by controlling the thickness Hb of the first positive electrode material active layer to 20-70 μm, the amount of the first positive electrode active material can be within a more appropriate range, so that its performance, such as energy density and service life, can be fully exerted, and at the same time, the probability of the occurrence of its side reactions leading to the deterioration of battery performance and safety performance can be reduced. By controlling the thickness Ha of the second positive electrode active material layer to 5-60 μm, the average transmission distance of the entire second positive electrode active material layer is within a smaller range, which is beneficial to its own ion transmission rate, and at the same time, it can reduce the weakening of the ion transmission capacity of the first positive electrode active material layer, thereby achieving better rate performance. In addition, the amount of the second positive electrode active material can be within a more appropriate range, so that its performance, such as safety performance, can be fully exerted.

[0017] In some embodiments, the thickness Hb of the first cathode material active layer is 25 to 55 μm; and / or

[0018] The thickness Ha of the second positive electrode active material layer is 20 to 50 μm.

[0019] In some embodiments, the first cathode active material comprises a ternary system material; and / or

[0020] The second positive electrode active material includes a polyanion positive electrode material.

[0021] In the above implementation process, polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet have both higher safety performance and higher energy density.

[0022] In some embodiments, the polyanion positive electrode material includes LiMPO4, M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping.

[0023] Optionally, the first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.

[0024] Optionally, the second doping element includes one or more elements of B, S, Si and N.

[0025] Optionally, the polyanion cathode material includes Li 1+x Mn 1-y A y P 1-z R zO4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0026] Optionally, the polyanion cathode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

[0027] In some embodiments, the polyanionic cathode material further has a coating layer comprising carbon.

[0028] In the above implementation process, the conductivity of the positive electrode active material is improved by introducing a carbon-containing coating layer. At this time, the structure of the positive electrode active material is actually a core-shell structure with LiMPO4 as the core and the surface of the core covered with a coating layer.

[0029] In some embodiments, the ternary system material includes nickel-cobalt-manganese ternary material and modified materials thereof and nickel-cobalt-aluminum ternary material and modified materials thereof.

[0030] In the above implementation process, the modified material of the nickel-cobalt-manganese ternary material and the modified material of the nickel-cobalt-aluminum ternary material refer to materials obtained by doping or coating the nickel-cobalt-manganese ternary material or the nickel-cobalt-aluminum ternary material, respectively.

[0031] In some embodiments, the weight percentage wCo of the Co element in the ternary system material and the thickness Hb of the second positive electrode active material layer in μm satisfy: 2%<wCo≤15%, 0.04 <wCo×Hb / 10≤1.05。

[0032] In the above implementation process, the content of Co element and the rate performance are positively correlated to a certain extent. The higher the content of Co, the better the corresponding rate performance. Controlling the proportion of Co element to be 2% - 15% can balance the rate performance and cost control. Controlling the relationship between the proportion of Co element and the thickness of the second positive electrode active material layer to satisfy 0.04 < wCo×Hb / 10 ≤ 1.05 can ensure an appropriate content of Co element in the second positive electrode active material layer, which is beneficial to the rate performance of the entire positive electrode sheet.

[0033] In some embodiments, the weight percentage wCo of Co element in all elements of the ternary system material and the thickness Hb of the first positive electrode active material layer in μm satisfy: 3% < wCo ≤ 12.5%, 0.3 < w×Hb / 1000 ≤ 0.7.

[0034] In a second aspect, the present application provides a positive electrode sheet, which includes a positive electrode active material layer and a current collector. The positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer. The first positive electrode active material layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on the surface of the first positive electrode active material layer away from the current collector; the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a ternary system material, the second positive electrode active material layer includes a second positive electrode active material, the second positive electrode active material includes a polyanion positive electrode material, the electronic conductivity of the second positive electrode active material is greater than that of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material at 8 MPa in Ω·cm, the powder resistivity r2 of the second positive electrode active material at 8 MPa in Ω·cm, the weight ratio w1 of the first positive electrode active material in the positive electrode sheet, and the weight ratio w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

[0035] In the technical solution of the embodiment of the present application, by controlling the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material to satisfy 0<(w2×r2) / (w1×r1)<0.5, the difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer is reduced, thereby reducing the electronic conduction polarization between the two layers, which is beneficial to the rate performance of the entire positive electrode sheet. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle. In addition, polyanion positive electrode materials generally exhibit good safety performance, and ternary system materials generally exhibit high energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet have both high safety performance and high energy density. In addition, a second positive electrode active material layer with weaker ion transport performance is arranged on the surface of the first positive electrode active material layer. When used as a battery, the second positive electrode active material layer is closer to the negative electrode sheet, making its ion transport path shorter, which is beneficial to improving its ion transport rate and thus improving its rate performance.

[0036] In a third aspect, the present application provides a pole piece assembly, a pole piece assembly isolation membrane, and a positive pole piece and a negative pole piece respectively arranged on two surfaces of the isolation membrane, wherein the positive pole piece includes the positive pole piece provided in the first aspect or the second aspect.

[0037] In some embodiments, the relationship between the closest distance H0 between the positive electrode sheet and the negative electrode sheet, the thickness Hb of the first positive electrode material active layer and the thickness Ha of the second positive electrode material satisfies:

[0038] In the above implementation process, by controlling the relationship between the shortest distance H0 between the positive electrode sheet and the negative electrode sheet, the thickness Hb of the active layer of the first positive electrode material and the thickness Ha of the second positive electrode material, The value is 1.3 to 6.8; it can reduce the weakening of the ion transmission capacity of the first positive electrode active material layer by the second positive electrode active material layer, thereby achieving better rate performance, wherein the closest distance H0 between the positive electrode sheet and the negative electrode sheet can be understood as the thickness of the isolation membrane to a certain extent.

[0039] In a fourth aspect, the present application provides a battery cell, the battery cell comprising the positive electrode sheet provided in the first aspect or the second aspect, or the electrode sheet assembly provided in the third aspect.

[0040] In a fifth aspect, the present application provides a battery, comprising the battery cell provided in the fourth aspect.

[0041] In a sixth aspect, the present application provides an electrical device, which includes the battery cell provided in the fourth aspect or the battery provided in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0043] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;

[0044] Figure 2 A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application;

[0045] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application;

[0046] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application;

[0047] Figure 5 A schematic diagram of the structure of a pole piece assembly provided in some embodiments of the present application;

[0048] Figure 6 A first structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;

[0049] Figure 7 A second structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;

[0050] Figure 8 A flow chart of a method for preparing a positive electrode sheet provided in some embodiments of the present application.

[0051] The reference numerals in the specific implementation manner are as follows:

[0052] 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 231-positive electrode sheet; 2311-positive current collector; 2312-positive active material layer; 2312a-first positive active material layer; 2312b-second positive active material layer; 232-negative electrode sheet; 233-separation membrane; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION

[0053] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0055] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0057] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0058] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0059] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0060] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0061] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0062] The power battery can be a lithium-ion battery, which is widely used in portable electronic devices, electric vehicles and other fields. In the production process of lithium-ion secondary battery electrode plates, a single-layer coating is usually used to coat the required active material on the current collector. With the increase in energy density and safety performance requirements, some people have proposed the use of positive electrode active materials with high energy density characteristics such as ternary system materials and positive electrode active materials with high safety performance characteristics such as polyanion positive electrode materials to take into account energy density and safety performance.

[0063] However, when a positive electrode active material with high energy density characteristics and a positive electrode active material with high safety performance characteristics are directly incorporated into a positive electrode active material layer, current unevenness is likely to occur between the two positive electrode active materials in the positive electrode active material layer. This phenomenon will cause the positive electrode sheet to decay rapidly in the early stage of the cycle, which will have a great impact on the cycle retention rate of the positive electrode sheet.

[0064] In order to further improve the problem of rapid attenuation of the electrode in the early stage of the cycle, the two active materials can be layered. However, after the layered arrangement, the conductivity difference between the two layers of positive electrode active material is large, so that the positive electrode still has the problem of low rate performance.

[0065] Based on the above considerations, in order to reduce the conductivity difference between each positive electrode active material layer and improve its rate performance. The present application proposes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the ion transmission capacity of the second positive electrode active material is less than the ion transmission capacity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

[0066] In such a positive electrode sheet, by controlling the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material, To reduce the difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer, thereby reducing the electronic conduction polarization between the two layers, which is beneficial to the rate performance of the entire positive electrode sheet. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle.

[0067] The positive electrode sheet can be used to prepare an electrode assembly, which can be used, but not limited to, in electrical devices such as vehicles, ships or aircraft. A power supply system of the electrical device can be composed of a battery cell, a secondary battery, etc. disclosed in the present application, so that it is conducive to giving full play to the effect of the positive electrode material with a high ultimate compaction density on the compaction density of the entire positive electrode active material layer, achieving a good improvement in the compaction density of the entire positive electrode active material layer, thereby improving the energy density of the positive electrode sheet and achieving an increase in the capacity of the battery cell.

[0068] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0069] For the convenience of description, the following embodiments are described by taking a vehicle as an example of an electrical device in an embodiment of the present application.

[0070] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000.

[0071] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .

[0072] In the present application, the secondary battery 100 refers to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, a battery module, etc. The secondary battery 100 can include a box 10 for encapsulating multiple battery cells 20, and the box 10 can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0073] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .

[0074] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.

[0075] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.

[0076] In the secondary battery 100, there are multiple battery cells 20, and the multiple battery cells 20 can be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in mixed connection, and then the whole body formed by the multiple battery cells 20 is accommodated in the box 10; of course, multiple battery cells 20 can also be connected in series, in parallel, or in mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in mixed connection to form a whole body, and accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular, or other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.

[0077] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .

[0078] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .

[0079] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.

[0080] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0081] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.

[0082] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, and the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.

[0083] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.

[0084] Figure 5For a schematic diagram of the structure of the pole piece assembly provided in some embodiments of the present application, please refer to Figure 5 The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet 232 and a separator 233. The positive electrode sheet 231 includes a positive electrode collector 2311 and a positive electrode active material layer 2312. The positive electrode active material layer 2312 is coated on the surface of the positive electrode collector 2311. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 protrudes from the positive electrode collector 2311 coated with the positive electrode active material layer 2312. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 serves as a positive electrode tab.

[0085] The negative electrode sheet 232 includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. In order to ensure that a large current passes without melting, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the isolation film 233 may be PP (polypropylene) or PE (polyethylene), etc. In addition, the electrode assembly 23 may be a wound electrode assembly or a laminated electrode assembly, and the embodiments of the present application are not limited thereto.

[0086] Figure 6 This is a first structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application. Figure 7 A second structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application; see Figure 6 and Figure 7 , the embodiment of the present application provides a positive electrode sheet, the positive electrode sheet 231 includes a positive electrode active material layer 2312, the positive electrode active material layer 2312 includes a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b, the first positive electrode active material layer 2312a includes a first positive electrode active material, the second positive electrode active material layer 2312b includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the ion transport capacity of the second positive electrode active material is less than the ion transport capacity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet 231, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet 231 satisfy the following relationship:

[0087] The positive electrode active material layer 2312 is attached to at least part of the surface of the positive electrode collector 2311. The first positive electrode active material layer 2312a and the second active material layer in the positive electrode active material layer 2312 can both be in direct contact with the positive electrode collector 2311. In other words, the positional relationship between the first positive electrode active material layer 2312a, the second active material layer and the positive electrode collector 2311 can be: the first positive electrode active material layer 2312a is attached to the positive electrode collector 2311, and the second positive electrode active material layer 2312b is attached to the surface of the first positive electrode active material layer 2312a facing away from the positive electrode collector 2311; it can also be: the second positive electrode active material layer 2312b is attached to the positive electrode collector 2311, and the first positive electrode active material layer 2312a is attached to the surface of the second positive electrode active material layer 2312b facing away from the positive electrode collector 2311.

[0088] The material of the positive electrode current collector 2311 may be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Figure 6 In one embodiment, a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b are sequentially disposed on one surface of the positive electrode current collector 2311; please continue to refer to Figure 7 In another embodiment, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b are sequentially disposed on both surfaces of the positive electrode current collector 2311. It should be noted that this is only an example of how this solution can be implemented. In other embodiments, the positions of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b may be swapped.

[0089] For lithium-ion batteries, the first positive electrode active material and the second positive electrode active material in the first positive electrode active material and the second positive electrode active material refer to substances capable of inserting and extracting lithium ions.

[0090] Powder resistivity, also known as powder resistivity, is the ratio between actual resistance value and theoretical resistance value. It is an indicator used to indicate the ability of powder materials to conduct current.

[0091] By controlling the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material to satisfy To reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, and further reduce the electronic conduction polarization between the two layers, which is beneficial to the rate performance of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby enabling the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.

[0092] Exemplarily, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8 MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8 MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet 231, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet 231 satisfy

[0093] etc., and it may be any value in the range of 0 to 0.5.

[0094] In the technical solutions of some embodiments of the present application, the powder resistivity r1 of the first positive electrode active material in Ω·cm, the powder resistivity r2 of the second positive electrode active material in Ω·cm, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet 231, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet 231 satisfy the following relationship: By controlling the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material to satisfy The difference in conductivity between the first positive electrode active material layer 2312 a and the second positive electrode active material layer 2312 b can be further reduced, which is more conducive to the performance of the rate performance of the entire positive electrode sheet 231 .

[0095] In the technical solutions of some embodiments of the present application, the powder resistivity of the first positive electrode active material is 500-80000Ω·cm at 8MPa; the powder resistivity of the second positive electrode active material is 5-120Ω·cm at 8MPa; the weight proportion of the first positive electrode active material in the positive electrode sheet 231 is 0.50-0.95; the weight proportion of the second positive electrode active material in the positive electrode sheet 231 is 0.05-0.50.

[0096] For example, at 8MPa, the powder resistivity of the first positive pole active material can be 500Ω·cm、1000Ω·cm、1500Ω·cm、2000Ω·cm、2500Ω·cm、3000Ω·cm、3500Ω·cm、4000Ω·cm、4500Ω·cm、5000Ω·cm、5500Ω·cm m、6000Ω·cm、6500Ω·cm、7000Ω·cm、7500Ω·cm、8000Ω·cm、8500Ω·cm、9000Ω·cm、9500Ω·cm、10000Ω·cm、10500Ω·cm、11000Ω·cm、11500Ω·cm、12000Ω·cm、1 2500Ω·cm、13000Ω·cm、13500Ω·cm、14000Ω·cm、14500Ω·cm、15000Ω·cm、15500Ω·cm、16000Ω·cm、16500Ω·cm、17000Ω·cm、17500Ω·cm、18000Ω·cm、18500Ω ·cm、19000Ω·cm、19500Ω·cm、20000Ω·cm、20500Ω·cm、21000Ω·cm、21500Ω·cm、22000Ω·cm、22500Ω·cm、23000Ω·cm、23500Ω·cm、24000Ω·cm、24500Ω·cm、2 5000Ω·cm、25500Ω·cm、26000Ω·cm、26500Ω·cm、27000Ω·cm、27500Ω·cm、28000Ω·cm、28500Ω·cm、29000Ω·cm、29500Ω·cm、30000Ω·cm、30500Ω·cm、31000Ω·cm Ω·cm、31500Ω·cm、32000Ω·cm、32500Ω·cm、33000Ω·cm、33500Ω·cm、34000Ω·cm、34500Ω·cm、35000Ω·cm、35500Ω·cm、36000Ω·cm、36500Ω·cm、37000Ω·cm、 37500Ω·cm、38000Ω·cm、38500Ω·cm、39000Ω·cm、39500Ω·cm、40000Ω·cm、40500Ω·cm、41000Ω·cm、41500Ω·cm、42000Ω·cm、42500Ω·cm、43000Ω·cm、43500Ω·cm Ω·cm、44000Ω·cm、44500Ω·cm、45000Ω·cm、45500Ω·cm、46000Ω·cm、46500Ω·cm、47000Ω·cm、47500Ω·cm、48000Ω·cm、48500Ω·cm、49000Ω·cm、49500Ω·cm、50000Ω·cm, 50500Ω·cm, 51000Ω·cm, 51500Ω·cm, 52000Ω·cm, 52500Ω·cm, 53000Ω·cm, 53500Ω·cm , 54000Ω·cm, 54500Ω·cm, 55000Ω·cm, 55500Ω·cm, 56000Ω·cm, 56500Ω·cm, 57000Ω·cm, 57500Ω·cm , 58000Ω·cm, 58500Ω·cm, 59000Ω·cm, 59500Ω·cm, 60000Ω·cm, 60500Ω·cm, 61000Ω·cm, 61500Ω·c m, 62000Ω·cm, 62500Ω·cm, 63000Ω·cm, 63500Ω·cm, 64000Ω·cm, 64500Ω·cm, 65000Ω·cm, 65500Ω·c m, 66000Ω·cm, 66500Ω·cm, 67000Ω·cm, 67500Ω·cm, 68000Ω·cm, 68500Ω·cm, 69000Ω·cm, 69500Ω· cm, 70000Ω·cm, 70500Ω·cm, 71000Ω·cm, 71500Ω·cm, 72000Ω·cm, 72500Ω·cm, 73000Ω·cm, 73500Ω· cm, 74000Ω·cm, 74500Ω·cm, 75000Ω·cm, 75500Ω·cm, 76000Ω·cm, 76500Ω·cm, 77000Ω·cm, 77500Ω·cm, 78000Ω·cm, 78500Ω·cm, 79000Ω·cm, 79500Ω·cm or 80000Ω·cm, etc., and it can also be any value in the range of 500 to 80000Ω·cm. At 8 MPa, the powder resistivity of the second positive electrode active material can be 5Ω·cm, 10Ω·cm, 15Ω·cm, 20Ω·cm, 25Ω·cm, 30Ω·cm, 35Ω·cm, 40Ω·cm, 45Ω·cm, 50Ω·cm, 55Ω·cm, 60Ω·cm, 65Ω·cm, 70Ω·cm, 75Ω·cm, 80Ω·cm, 85Ω·cm, 90Ω·cm, 95Ω·cm, 100Ω·cm, 105Ω·cm, 110Ω·cm, 115Ω·cm or 120Ω·cm, etc., and it can also be any value in the range of 5 to 120Ω·cm. The weight proportion of the first positive electrode active material in the positive electrode sheet 231 can be 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 or 0.95, etc., and can also be any value in the range of 0.50 to 0.95. The weight proportion of the second positive electrode active material in the positive electrode sheet 231 can be 0.05, 0.10, 0.15, 0.20, 0.25,0.30, 0.35, 0.40, 0.45 or 0.50, etc. It can also be any value in the range of 0.05 to 0.50.

[0097] In the technical solutions of some embodiments of the present application, the positive electrode sheet 231 also includes a current collector, the first positive electrode material active layer is arranged on at least one surface of the current collector, and the second positive electrode active material layer 2312b is arranged on the surface of the first positive electrode active material layer 2312a away from the current collector. By arranging the second positive electrode active material layer 2312b with weaker ion transmission performance on the surface of the first positive electrode active material layer 2312a, when used as a battery, the second positive electrode active material layer 2312b is closer to the negative electrode sheet 232, so that its ion transmission path is shorter, which is conducive to improving the overall ion transmission rate of the positive electrode active material layer, thereby improving its rate performance. At the same time, when the material of the first positive electrode material active layer 2312a is a material that is prone to side reactions, such as a ternary system material, this method can reduce the possibility of side reactions, which is more conducive to the electrochemical performance of the positive electrode sheet.

[0098] In the technical solutions of some embodiments of the present application, the thickness Hb of the first positive electrode material active layer is 20-70 μm; the thickness Ha of the second positive electrode active material layer 2312b is 5-60 μm. By controlling the thickness Hb of the first positive electrode material active layer to be 20-70 μm, the amount of the first positive electrode active material can be within a more appropriate range, so that its performance, such as energy density and service life, can be fully exerted, and at the same time, the probability of the occurrence of its side reactions causing the battery performance and safety performance to deteriorate can be reduced. By controlling the thickness Ha of the second positive electrode active material layer 2312b to be 5-60 μm, the average transmission distance of the entire second positive electrode active material layer 2312b is within a smaller range, which is beneficial to its own ion transmission rate, and at the same time, it can reduce the weakening of the ion transmission capacity of the first positive electrode active material layer 2312a, thereby achieving better rate performance. In addition, the amount of the second positive electrode active material can be within a more appropriate range, so that its performance, such as safety performance, can be fully exerted.

[0099] For example, the thickness Hb of the first positive electrode material active layer can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm or 70 μm, etc., and it can also be any value in the range of 20 to 70 μm. The thickness Ha of the second positive electrode active material layer 2312b can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm, etc., and it can also be 5 to 60 μm.

[0100] In the technical solutions of some embodiments of the present application, the thickness Hb of the first positive electrode material active layer is 25 to 55 μm; the thickness Ha of the second positive electrode active material layer 2312b is 20 to 50 μm.

[0101] For example, the thickness Hb of the first positive electrode material active layer can be 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm and 55 μm, etc., and can also be any value in the range of 25 to 55 μm. The thickness Ha of the second positive electrode active material layer 2312b can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm and 50 μm, etc., and can also be any value in the range of 20 to 50 μm.

[0102] In the technical solutions of some embodiments of the present application, the first positive electrode active material includes a ternary system material; the second positive electrode active material includes a polyanion positive electrode material.

[0103] Polyanion positive electrode materials are a general term for a series of compounds containing tetrahedral or octahedral anion structural units (XOm)n-. They have the advantages of high charge and discharge voltage, large energy storage capacity, fast charge and discharge capability and good cycle stability. Their synthesis methods mainly include: high temperature solid phase method, sol-gel method, hydrothermal method, electrospinning method, etc.

[0104] Ternary system materials usually include two types: NCA and NCM. Among them, NCA is widely used because of its long life, large capacity, high energy density and other characteristics, but its specific heat capacity is relatively low; NCM combines the advantages of three types of positive electrode materials: lithium cobalt oxide, lithium nickel oxide and lithium manganese oxide, and has obvious ternary synergistic effect. NCM can usually be expressed as: LiNi x Co y Mn z O2.

[0105] Polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet 231 have both higher safety performance and higher energy density.

[0106] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes a polyanion positive electrode material. Optionally, the polyanion positive electrode material includes LiMPO4, and M includes Mn and non-Mn elements.

[0107] It should be noted that the above-mentioned LiMPO4 is not a specific molecular structure formula, but a general expression of lithium manganese phosphate.

[0108] In the technical solutions of some embodiments of the present application, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.

[0109] In the technical solutions of some embodiments of the present application, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.

[0110] In the technical solutions of some embodiments of the present application, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg.

[0111] In the technical solutions of some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N.

[0112] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O4, Li 1+x Mn 1-y A y P 1-z R z In O4, x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0113] In the technical solutions of some embodiments of the present application, the compound Li 1+x Mn 1-y AHr 1-z The preparation method of RzO4 may include the following steps:

[0114] (1) dissolving a manganese source, a source of an element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with the element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with the element A;

[0115] (2) adding a lithium source, a phosphorus source, an element R source, a solvent, and the manganese salt doped with element A obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;

[0116] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;

[0117] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.

[0118] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.

[0119] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. The source of element R is selected from at least one of sulfate, borate, nitrate and silicate of element R. The source of element A is selected from at least one of simple substance, oxide, phosphate, oxalate, carbonate and sulfate of A.

[0120] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

[0121] It should be noted that Li h A i Mn 1-j B j P 1-k C k O 4-l D l The compound is actually a specific LiMPO4 material. Its preparation method can refer to Li 1+x Mn 1-y A y P 1-z R z O4, no limitation is made here.

[0122] Below is Li0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 The preparation process is further explained: 1. Preparation of doped manganese oxalate: 1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O are fully mixed in a mixer for 6 hours. The mixture is transferred to a reactor, and 10L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) are added. The reactor is heated to 80°C and stirred at 600 rpm for 6 hours. The reaction is terminated (no bubbles are generated) to obtain a Fe-doped manganese oxalate suspension. The suspension is then filtered, the filter cake is dried at 120°C, and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles of about 100 nm. 2. Preparation of doped lithium manganese phosphate: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, an aqueous phosphoric acid solution containing 0.999 mol of phosphoric acid at a concentration of 85%, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90% volume) + hydrogen (10% volume), sinter the above powder at 700°C for 10 hours to obtain carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 .

[0123] In the technical solutions of some embodiments of the present application, the second positive electrode active material further has a carbon-containing coating layer.

[0124] The introduction of the carbon-containing coating layer improves the conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually a core-shell structure with LiMPO4 as the core and the surface of the core covered with the coating layer.

[0125] In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before adding the materials. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0126] In addition, due to the different preparation processes and conditions of the materials, the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y A y P 1-z R z The molar content of the O element in O4 is not strictly 4.

[0127] For example, the second positive electrode active material may be LiFePO4, LiMn 0.1 Fe 0.9 PO4、LiMn 0.2 Fe 0.8 PO4、LiMn 0.3 Fe 0.7 PO4、LiMn 0.4 Fe 0.6 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.7 Fe 0.3 PO4、LiMn 0.8 Fe 0.2 PO4、LiMn 0.9 Fe 0.1 PO4, LiMnPO4, LiMn 0.5 Al 0.5 P 0.5 B 0.5 O4、LiMn 0.5 Mg 0.5 P 0.5 S 0.5 O4, etc., M in LiMPO4 includes Mn and non-Mn elements, non-Mn elements include one or two of the first doping element and the second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping. The first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; the second doping element includes one or more elements of B, S, Si and N.

[0128] In the technical solutions of some embodiments of the present application, the ternary system materials include nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials. Among them, the ternary system materials include nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials; for example, the chemical formula of the ternary system material is LiNi x Co y Mn zO2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1, such as LiNi 0.4 Co 0.2 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2 and LiNi 0.7 Co 0.15 Mn 0.15 O2, etc.

[0129] It should be noted that the above enumeration of the first positive electrode active material and the second positive electrode active material is only for illustrative purposes to show that the present solution can be implemented, and does not limit the present solution. The implementation of the present solution only requires that the first positive electrode active material and the second positive electrode active material meet the corresponding electronic conductivity requirements. In other embodiments, those skilled in the art can select the specific substances of the first positive electrode active material and the second positive electrode active material according to actual needs, such as the above-listed materials and their modified substances, and the modification includes doping or coating, etc., or select other materials that meet the electronic conductivity requirements of the present application.

[0130] In the technical solutions of some embodiments of the present application, the weight percentage wCo of Co element in all elements in the ternary system material and the thickness Hb of the second positive electrode active material layer 2312b in μm satisfy: 2% < wCo ≤ 15%, 0.04 < wCo × Hb / 10 ≤ 1.05. The content of Co element and the rate performance are positively correlated to a certain extent. The higher the content of Co, the better the corresponding rate performance. Controlling the proportion of Co element to be 2% - 15% can balance the rate performance and cost control. Controlling the relationship between the proportion of Co element and the thickness of the second positive electrode active material layer 2312b to satisfy 0.04 < wCo × Hb / 10 ≤ 1.05 can make the content of Co element in the second positive electrode active material layer 2312b appropriate, which is beneficial to the rate performance of the entire positive electrode sheet 231.

[0131] For example, the weight proportion wCo of the Co element in the ternary system material can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., and it can also be any value in the range of 2% to 15%. The value of the relationship w×Hb / 1000 satisfied by the weight proportion wCo of the Co element in the ternary system material and the thickness Hb of the second positive electrode active material layer 2312b can be 0.04, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00 or 1.05, etc., and it can also be any other value in the range of 0.04 to 1.05.

[0132] In the technical solutions of some embodiments of the present application, the weight percentage wCo of the Co element in the ternary system material and the thickness Hb of the first positive electrode active material layer 2312a in μm satisfy: 3%<wCo≤12.5%, 0.3 <wCo×Hb / 10≤0.7。

[0133] After the above introduction to the material and structure of the positive electrode sheet 231 , the preparation method of the positive electrode sheet 231 will be specifically introduced below.

[0134] The preparation method of the positive electrode sheet 231 includes the following steps: preparing a positive electrode active material layer 2312 on a positive electrode current collector 2311, wherein the preparation order of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b in the positive electrode active material layer 2312 is not limited, and may be: the first positive electrode active material layer 2312a is arranged on at least a portion of the surface of the positive electrode current collector 2311, and the second positive electrode active material layer 2312b is arranged on at least a portion of the surface of the first positive electrode active material away from the positive electrode current collector 2311; or: the second positive electrode active material layer 2312b is arranged on at least a portion of the surface of the positive electrode current collector 2311, and the first positive electrode active material layer 2312a is arranged on the second positive electrode active material layer 2312b away from At least a portion of the surface of the positive electrode current collector 2311; the first positive electrode active material layer 2312a includes a first positive electrode active material, the second positive electrode active material layer 2312b includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the ion transport capacity of the second positive electrode active material is less than the ion transport capacity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet 231, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet 231 satisfy the following relationship:

[0135] The method satisfies the following conditions by controlling the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material: To reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, and further reduce the electronic conduction polarization between the two layers, which is beneficial to the rate performance of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby enabling the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.

[0136] Figure 8 For a flow chart of a method for preparing the positive electrode sheet 231 provided in some embodiments of the present application, please refer to Figure 8 The present application embodiment provides a method for preparing a positive electrode sheet 231, the method comprising:

[0137] S110, preparing a first positive electrode active slurry: dispersing a first positive electrode active material, a binder and a conductive agent in a solvent to form a first positive electrode active slurry. The first positive electrode active material may be the first positive electrode active material described above, for example, a material having a chemical formula of LiNi x Co y Mn z O2, (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) ternary system material, optionally, a small amount of other positive electrode active materials may be added.

[0138] For the specific selection of the ternary system material, reference may be made to the selection of the ternary system material in the first positive electrode active material layer 2312 a in the aforementioned positive electrode sheet 231 , which will not be described in detail here.

[0139] The binder may be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol and polyvinyl butyral. The conductive agent may be at least one of conductive carbon black, carbon fiber, carbon nanotube, Ketjen black, graphene or acetylene black. The solvent may be one or more of dimethyl glutarate and N-methyl pyrrolidone. A leveling agent, a dispersant, etc. may also be added to the first positive electrode active slurry.

[0140] S120, preparing a second positive electrode active slurry: dispersing a second positive electrode active material, a binder and a conductive agent in a solvent to form a second positive electrode active slurry. The second positive electrode active material may be the second positive electrode active material described above, for example, a material having a chemical formula of LiMn a Fe 1-a PO4, (0≤a≤1) polyanion positive electrode material, optionally, a small amount of other positive electrode active materials may be added.

[0141] For the specific selection of the polyanion positive electrode material, reference may be made to the selection of the polyanion positive electrode material in the second positive electrode active material layer 2312 b in the aforementioned positive electrode sheet 231 , which will not be described in detail here.

[0142] The binder, the conductive agent and the solvent may be the binder, the conductive agent and the solvent in the first positive electrode active slurry, etc. The binder in the first positive electrode active slurry may be the same as or different from the binder in the second positive electrode active material; the conductive agent in the first positive electrode active slurry may be the same as or different from the conductive agent in the second positive electrode active material; the solvent in the first positive electrode active slurry may be the same as or different from the solvent in the second positive electrode active material. At the same time, a leveling agent, a dispersant, etc. may also be added to the second positive electrode active slurry, which is not limited in this application.

[0143] S130, preparing the first positive electrode active material layer 2312a: coating the first positive electrode active slurry on the surface of the positive electrode current collector 2311, and then drying to form the first positive electrode active material layer 2312a. The coating can be applied to one surface or both surfaces of the positive electrode current collector 2311 according to requirements.

[0144] The coating method may be: scraping, roller coating, slit coating, etc., which is not limited in this application. It should be noted that step S120 and step S130 can be interchanged or performed simultaneously, which is not limited in this application.

[0145] S140, preparing the second positive electrode active material layer 2312b: coating the second positive electrode active slurry on the surface of the first positive electrode active material layer 2312a, and then drying to form the second positive electrode active material layer 2312b. During coating, the second positive electrode active material layer 2312b can be formed on the surface of the first positive electrode active material layer 2312a according to the situation of the first positive electrode active material layer 2312a.

[0146] S150 , rolling the second positive electrode active material layer 2312 b to obtain the positive electrode sheet 231 .

[0147] It should be noted that the above is only an example of sequentially arranging the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b on the positive electrode current collector 2311. In other embodiments, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be exchanged.

[0148] After the positive electrode sheet 231 is prepared, the first isolation film 233, the positive electrode sheet 231, the second isolation film 233 and the negative electrode sheet 232 are stacked in sequence, wound to form a wound flat structure, and then hot pressed to obtain a wound electrode assembly; or, after the positive electrode sheet 231 is prepared, the positive electrode sheet 231, the isolation film 233, the negative electrode sheet 232, the isolation film 233, and so on, are stacked in sequence to form a stacked electrode assembly.

[0149] The electrode assembly 23 can be used to prepare a battery cell 20 , and the battery cell 20 can be used to prepare a secondary battery 100 and provide electric energy to an electric device.

[0150] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.

[0151] Examples and Comparative Examples

[0152]

Preparation of positive electrode

[0153] Preparation of the first positive electrode active material layer: the first positive electrode active material NCM, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP), wherein the mass proportion of the binder polyvinylidene fluoride (PVDF) is 2.5%, and the mixture is stirred and mixed to obtain the first coating layer slurry; then the slurry is mixed at 200 mg / 1540.25 mm 2 The mass of the positive electrode active material is evenly coated on the positive electrode current collector and dried to obtain a first positive electrode active material layer.

[0154] Preparation of the second positive electrode active material layer: The second positive electrode active material LiMn 0.6 Fe 0.4 PO4, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1:2.5, and stirred and mixed to obtain a second coating layer slurry; then the slurry was added at 90 mg / 1540.25 mm 2 The mass is evenly coated on the first positive electrode active material layer, and after drying, it is rolled and die-cut to obtain a lithium-ion battery positive electrode sheet.

[0155]

Preparation of negative electrode sheet

[0156] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a mass ratio of 90:5:3:2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.

[0157]

Preparation of electrolyte

[0158] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1 / 1 / 1, 1 mol / L LiPF6 lithium salt was added and dispersed evenly, and then 5% fluoroethylene carbonate was dissolved in the above organic solvents and stirred evenly to obtain an electrolyte.

[0159]

Isolation film

[0160] A polyethylene film was used as the separator, and its thickness was 7 μm.

[0161]

Preparation of lithium-ion batteries

[0162] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are wound to form the corresponding battery cell, and the battery cell is hot pressed at 90°C, followed by ultrasonic welding of the positive and negative pole tabs. The positive electrode uses aluminum pole tabs, and the negative electrode uses copper pole tabs. The positive and negative pole tabs are located on the same side of the battery cell. The battery cell after the pole tab welding is placed in an aluminum shell of appropriate size for soft connection and top cover welding. The battery cell is vacuum dried at 175°C for 24 hours, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then goes through the processes of static, formation, aging, exhaust, secondary sealing, capacity testing, etc. to obtain a lithium-ion battery product.

[0163] The main parameters of each embodiment and comparative example are shown in the following table:

[0164]

[0165] In the table above, the chemical formula of the NCM material with a wCo value of 0.08 is LiNi 0.55 Co 0.12 Mn 0.33 The chemical formula of NCM material with O2 and wCo values ​​of 0.01 is LiNi 0.55 Co 0.01 Mn 0.43 The chemical formula of NCM material with O2 and wCo value of 0.02 is LiNi 0.55 Co 0.04 Mn 0.41 The chemical formula of NCM material with O2 and wCo value of 0.15 is LiNi 0.65 Co 0.18 Mn 0.17 The chemical formula of NCM material with O2 and wCo value of 0.2 is LiNi 0.65 Co 0.25 Mn 0.10 O2.

[0166] The positive electrode material powder resistivity test includes: the test equipment is Yuanneng Technology PRCD2100 powder resistivity tester, first weigh 0.2g of sample and add it to the sample cavity of the equipment mold, put the mold into the pre-compactor, turn on the pre-compactor to vibrate the powder, and then open the equipment software to start the test and get the test results.

[0167] The Co content test of NCM material includes: taking 0.4g of the electrode NCM material layer powder in a 25ml beaker, adding 2ml~5ml nitric acid, leaving it overnight, and then placing it on an electric hot plate, heating it at about 100°C (using a voltage-regulating transformer to adjust the input voltage and temperature control), adding 0.5ml perchloric acid after the powder is digested, heating and digesting it at about 140°C until the white smoke is gone, and the residue should be white, otherwise nitric acid and perchloric acid should be added again to repeat the digestion, and finally using 7% (volume % of acid, the same below) hydrochloric acid to dissolve and extract, and after the volume is fixed to an appropriate volume depending on the content of the element to be tested, the mass fraction of Ni, Co, Mn, and Li is tested on the ICP-OES test instrument. The mass of different elements can be calculated based on the mass of the powder and the mass fraction of different elements, and then the molar amount can be calculated based on its molar mass. The Co content can be confirmed by the molar ratio of different elements.

[0168] Embodiment 26

[0169] This embodiment is the same as Embodiment 3 except that the positions of the first positive electrode material active layer and the second positive electrode active material layer are exchanged.

[0170] The performance test was performed on the batteries provided in each embodiment and comparative example, and the performance test specifically included:

[0171] The method of rate performance test is: in an environment of 25℃, charge and discharge test is carried out, and constant current discharge is carried out at a discharge current of 0.33C (i.e., the current value of the theoretical capacity is completely discharged within 3h) until the voltage is 2.5V. Then, constant current charging is carried out at a charging current of 0.33C to a voltage of 4.4V, and constant voltage charging is continued to be carried out to a current of 0.05C. At this time, the battery is in a fully charged state. After the fully charged battery cell is left to stand for 5 minutes, constant current discharge is carried out at a discharge current of 0.33C to 2.5V. The discharge capacity at this time is the actual capacity of the battery cell at 0.33C, recorded as C0. Then, the battery cell is charged to 4.4V at a constant current of 0.33C, and then constant voltage charging is carried out to a current of 0.05C, and it is left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C, and the discharge capacity C1 is recorded as the 1C discharge capacity. 1C rate capacity retention rate = (1C discharge capacity / 0.33C discharge capacity) × 100%.

[0172] The test results are shown in the following table:

[0173]

[0174]

[0175] It can be seen from the above table that the battery made of the electrode sheet provided in the embodiment of the present application has good rate performance, and the rate performance can reach more than 97%.

[0176] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material satisfy When the powder resistivity r1 of the first positive electrode active material, the powder resistivity r2 of the second positive electrode active material, the weight proportion w1 of the first positive electrode active material and the weight proportion w2 of the second positive electrode active material meet When the rate performance is better, it can reach more than 99%.

[0177] By comparing Example 3 with Examples 6 to 9, it can be seen that as the thickness Ha of the second positive electrode active material layer increases, the rate performance shows a trend of first increasing and then decreasing, and when the thickness Ha of the second positive electrode active material layer is in the range of 5 to 60 μm, it has good rate performance, which can reach more than 99.2%.

[0178] By comparing Example 3 with Examples 10 to 13, it can be seen that as the thickness Hb of the first positive electrode material active layer increases, the rate performance shows a trend of first increasing and then decreasing, and when the thickness Ha of the second positive electrode active material layer is in the range of 20 to 70 μm, it has good rate performance, which can reach more than 98.7%.

[0179] By comparing Example 3 with Examples 14 to 17, it can be obtained that the relationship between the closest distance H0 between the positive electrode sheet and the negative electrode sheet, the thickness Hb of the active layer of the first positive electrode material and the thickness Ha of the second positive electrode material The value of gradually increases, and the rate performance shows a trend of increasing first and then decreasing. The relationship between the closest distance H0 between the positive electrode sheet and the negative electrode sheet, the thickness Hb of the active layer of the first positive electrode material and the thickness Ha of the second positive electrode material is When the value is in the range of 1.3 to 6.8, it has good rate performance and can reach more than 98.9%.

[0180] By comparing Example 3 with Examples 18 to 21, it can be obtained that as the weight percentage wCo of the Co element in all elements in the ternary system material gradually increases, the rate performance shows a trend of first increasing and then decreasing, and when the weight percentage wCo of the Co element in all elements in the ternary system material is in the range of 0.02 to 0.15, it has good rate performance, which can reach more than 98.7%.

[0181] By comparing Example 3 with Examples 22 to 25, it can be obtained that as the value of the relationship between the proportion of the Co element and the thickness of the second positive electrode active material layer w×Hb / 10 gradually increases, the rate performance shows a trend of first increasing and then decreasing, and when the value of the relationship between the proportion of the Co element and the thickness of the second positive electrode active material layer w×Hb / 10 is in the range of 0.04 to 1.05, it has good rate performance, which can reach more than 98.6%.

[0182] By comparing Example 3 with Example 26, it can be seen that placing the ternary system material in the inner layer will make the entire positive electrode sheet have better rate performance.

[0183] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the ion transport capacity of the second positive electrode active material is less than the ion transport capacity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

2. The positive electrode sheet according to claim 1, characterized in that: The powder resistivity r1 of the first positive electrode active material in Ω·cm, the powder resistivity r2 of the second positive electrode active material in Ω·cm, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The powder resistivity of the first positive electrode active material is 500 to 80,000 Ω·cm at 8 MPa; and / or The powder resistivity of the second positive electrode active material is 5 to 120 Ω·cm at 8 MPa; and / or The weight proportion of the first positive electrode active material in the positive electrode sheet is 0.50 to 0.95; and / or The weight ratio of the second positive electrode active material in the positive electrode sheet is 0.05-0.

50.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode sheet further includes a current collector. The first positive electrode material active layer is disposed on at least one surface of the current collector. The second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector.

5. The positive electrode sheet according to claim 4, characterized in that: The thickness Hb of the first positive electrode material active layer is 20 to 70 μm; and / or The thickness Ha of the second positive electrode active material layer is 5 to 60 μm.

6. The positive electrode sheet according to claim 5, characterized in that: The thickness Hb of the first positive electrode material active layer is 25 to 55 μm; and / or The thickness Ha of the second positive electrode active material layer is 20 to 50 μm.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The first positive electrode active material comprises a ternary system material; and / or The second positive electrode active material includes a polyanion positive electrode material.

8. The positive electrode sheet according to claim 7, characterized in that: The ternary system materials include nickel-cobalt-manganese ternary materials and modified materials thereof and nickel-cobalt-aluminum ternary materials and modified materials thereof; and / or The polyanion positive electrode material includes LiMPO4, M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping.

9. The positive electrode sheet according to claim 8, characterized in that: The first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or The second doping element includes one or more elements selected from the group consisting of B, S, Si and N.

10. The positive electrode sheet according to claim 8, characterized in that: The polyanion positive electrode material includes Li 1+x Mn 1- y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

11. The positive electrode sheet according to claim 8, characterized in that: The polyanion positive electrode material includes Li h A i Mn 1- j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

12. The positive electrode sheet according to any one of claims 7 to 11, characterized in that: The polyanion positive electrode material also has a coating layer containing carbon.

13. The positive electrode sheet according to any one of claims 7 to 12, characterized in that: The weight percentage wCo of the Co element in the ternary system material and the thickness Hb of the second positive electrode active material layer in μm units satisfy: 2%<wCo≤15%, 0.04 <wCo×Hb / 10≤1.05。 14. The positive electrode sheet according to claim 13, characterized in that: The weight percentage wCo of the Co element in the ternary system material and the thickness Hb of the first positive electrode active material layer in μm satisfy: 3%<wCo≤12.5%, 0.3 <wCo×Hb / 10≤0.7。 15. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode active material layer and a current collector, the positive electrode active material layer comprises a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer is arranged on at least one surface of the current collector, and the second positive electrode active material layer is arranged on a surface of the first positive electrode active material layer away from the current collector; the first positive electrode active material layer comprises a first positive electrode active material, the first positive electrode active material comprises a ternary system material, the second positive electrode active material layer comprises a second positive electrode active material, the second positive electrode active material comprises a polyanion positive electrode material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the powder resistivity r1 of the first positive electrode active material in Ω·cm at 8MPa, the powder resistivity r2 of the second positive electrode active material in Ω·cm at 8MPa, the weight proportion w1 of the first positive electrode active material in the positive electrode sheet, and the weight proportion w2 of the second positive electrode active material in the positive electrode sheet satisfy the following relationship:

16. A pole piece assembly, characterized in that: The electrode assembly isolation film and the positive electrode sheet and the negative electrode sheet respectively arranged on the two surfaces of the isolation film, the positive electrode sheet includes the positive electrode sheet according to any one of claims 1 to 15.

17. The pole piece assembly according to claim 16, characterized in that: The relationship between the shortest distance H0 between the positive electrode sheet and the negative electrode sheet, the thickness Hb of the first positive electrode material active layer and the thickness Ha of the second positive electrode material satisfies:

18. A battery cell, characterized in that: The battery cell comprises the positive electrode sheet according to any one of claims 1 to 15 or the electrode sheet assembly according to claims 16 to 17.

19. A battery, characterized in that: The battery comprises the battery cell according to claim 18.

20. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 18 or the battery according to claim 19.

Citation Information

Patent Citations

  • Positive pole piece, preparation method thereof and battery

    CN115275108A

  • Positive pole piece, secondary battery and electric equipment

    CN116314602A

  • Positive electrode for secondary battery, and secondary battery

    US20200091515A1

  • Lithium-ion secondary battery and related preparation method thereof, battery module, battery pack and apparatus

    US20220123286A1